Making learning accessible: Multicultural learning using social media to run trans-national entrepreneurial “pop-up businesses” - Parry, Z.; Baird, Craig (IADIS, 2012)
Learning in multicultural contexts can compound teaching difficulties for the educator and students when introducing creative and experiential elements into the syllabus and pedagogy of an Entrepreneurship class. Having students from traditionally risk-averse cultures provides many opportunities for diverse points of view and innovative problem solving approaches, while also presenting potential risks if events don’t go according to plan. Identifying cultural behavioural issues that affect student interaction in experiential, creative learning experiences learning activities is paramount to making appropriate technology tool choices This case study documents the synergy and creativity that emerged from the use of social media tools to facilitate learning and teaching for students of entrepreneurship interacting across multiple countries, philosophies, languages and cultural expectations.